Safety Issues Referred to Induced Sheath Voltages in High-Voltage Power Cables—Case Study - Stanislaw Czapp; Krzysztof Dobrzynski (Applied Sciences, 2020)
Load currents and short-circuit currents in high-voltage power cable lines are sources of the induced voltages in the power cables’ concentric metallic sheaths. When power cables operate with single-point bonding, which is the simplest bonding arrangement, these induced voltages may introduce an electric shock hazard or may lead to damage of the cables’ outer non-metallic sheaths at the unearthed end of the power cable line. To avoid these aforementioned hazards, both-ends bonding of metallic sheaths is implemented but, unfortunately, it leads to increased power losses in the power cable line, due to the currents circulating through the sheaths. A remedy for the circulating currents is cross bonding—the most advanced bonding solution. Each solution has advantages and disadvantages. In practice, the decision referred to its selection should be preceded by a wide analysis. This paper presents a case study of the induced sheath voltages in a specific 110 kV power cable line. This power cable line is a specific one, due to the relatively low level of transferred power, much lower than the one resulting from the current-carrying capacity of the cables. In such a line, the induced voltages in normal operating conditions are on a very low level. Thus, no electric shock hazard exists and for this reason, the simplest arrangement—single-point bonding—was initially recommended at the project stage. However, a more advanced computer-based investigation has shown that in the case of the short-circuit conditions, induced voltages for this arrangement are at an unacceptably high level and risk of the outer non-metallic sheaths damage occurs. Moreover, the induced voltages during short circuits are unacceptable in some sections of the cable line even for both-ends bonding and cross bonding. The computer simulations enable to propose a simple practical solution for limiting these voltages. Recommended configurations of this power cable line—from the point of view of the induced sheath voltages and power losses—are indicated.